Early Biomarkers of Renal Damage in Relation to Arterial Stiffness and Inflammation in Male Coronary Artery Disease Patients - Kaido Paapstel; Mihkel Zilmer; Jaan Eha; Kaspar Tootsi; Anneli Piir; Jaak Kals (Karger Publishers, 2016)
Background/Aims: Plasma neutrophil gelatinase-associated lipocalin (NGAL), urinary liver-type fatty acid-binding protein (L-FABP) and urinary kidney injury molecule-1 (KIM-1) have emerged as promising biomarkers for both acute and chronic kidney injury that also provide prognostic value for cardiovascular morbidity and mortality. Our aim was to evaluate their relationships with arterial stiffness and inflammation in coronary artery disease (CAD) patients and in clinically healthy controls. Methods: We studied 52 patients with CAD (age 63.2 ± 9.2 years) and 41 healthy controls (age 60.1 ± 7.2 years). Urinary L-FABP and KIM-1 as well as serum NGAL, adiponectin and resistin levels were measured using the enzyme-linked immunosorbent assay method. The technique of applanation tonometry was used for non-invasive pulse wave analysis and pulse wave velocity assessments. Results: Urinary L-FABP and KIM-1 were independent determinants of cf-PWV for the CAD patients (R2=0.584, Pr=0.31, P=0.028) only for the patients, while NGAL correlated with WBC count (rho=0.29, P=0.038; r=0.35, P=0.029) and resistin (rho=0.60, PConclusion: Our findings suggest that urinary L-FABP and KIM-1 may be independently associated with aortic stiffness in individuals with CAD.